2023
DOI: 10.1039/d2tc04727f
|View full text |Cite
|
Sign up to set email alerts
|

Reversible human-temperature-responsive luminescence switching in a Mn(ii)-based metal halide

Abstract: The flexibility afforded by the modular structure confers fruitful unique properties to the organic-inorganic hybrid metal halides (OIMHs). Typically, stimuli-responsive materials have wide applications in thermal imaging, thermometer, and anti-counterfeiting....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 67 publications
(78 reference statements)
1
15
0
Order By: Relevance
“…Lei reported a family of OIMHs with reversible off–on switching luminescence, which can be used in water-jet rewritable printing, anticounterfeiting, and encryption and decryption . Although significant progress has been made, rewritable anticounterfeiting printing based on OIMHs as an emitter is still in its infancy and deserves to be thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Lei reported a family of OIMHs with reversible off–on switching luminescence, which can be used in water-jet rewritable printing, anticounterfeiting, and encryption and decryption . Although significant progress has been made, rewritable anticounterfeiting printing based on OIMHs as an emitter is still in its infancy and deserves to be thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…The PL properties come from the d–d transition of tetrahedral coordinated Mn 2+ , corresponding to the 3d 5 electronic transition of Mn 2+ from the excited state 4 T 1 to the ground state 6 A 1 . 46,54 The CIE chromaticity coordinates of ( R -HASD) 2 MnBr 4 and ( S -HASD) 2 MnBr 4 are (0.206, 0.697) and (0.211, 0.695), respectively, which are located in the green area shown in Fig. 5f.…”
Section: Resultsmentioning
confidence: 99%
“…39,40 Subsequently, many dielectric multifunctional materials emitting various colors, such as red, green, yellow, blue, and others, were explored, significantly enriching the development of fluorescent dielectric multifunctional materials. 38,[41][42][43][44][45] Luo et al also reported white light dielectric responsive lead-based materials, which have a warm white light a color temperature of 4423 K and have high color rendering index (CRI) of up to 86. 28 Despite these great advances, the single material simultaneously equipped with a dual channel optical/electrical response of dielectric switching response and intrinsic broadband white-light emission has been very rare and an ongoing challenge.…”
Section: Introductionmentioning
confidence: 99%